Omicron Positivity in Air of Hospital Settings Gathered COVID-19 Patients, Vaccinated/Unvaccinated Populations - Zeynep Ece Kuloğlu; Zeynep Bengi Eren; Bedirhan Haykar; Cansel Vatansever; Tayfun Barlas; Mert Ahmet Kuskucu; Gülen Güney-Esken; Füsun Can (Aerosol and Air Quality Research)
Abstract The Omicron variant spreads quicker than the earlier variants and can evade the immune response. The behavior changes and waning immunity could cause large numbers of COVID-19 infections and potential hospitalizations. Here, we present a cross-sectional/longitudinal study conducted in a tertiary hospital in Istanbul. In the cross-sectional part, we collected aerosol samples from clinical and public areas in the hospital. We performed qPCR and viral culture. In the pediatrics, outpatient clinic waiting room, where the children were without masks, and unvaccinated, 66% of the samples were positive for viral RNA. However, the positivity rate was 14% in the staff dining hall where everybody was without masks but fully vaccinated. The viral RNA was positive in 50% of the COVID-19 patient rooms, 33% of the febrile disease outpatient clinic, and 33% of the clinical laboratory waiting room. There was no viral growth in the culture of all samples. The highest viral load was detected in the COVID-19 patient room (3.60 × 1010 PFU m−3), followed by the pediatrics outpatient clinic waiting room (2.8 × 108 PFU m−3). In the longitudinal study, samples were collected 0, 2.5, 4.5, and 24 hours after a meeting in which all attendees were wearing masks and three participants were diagnosed with COVID-19. Only one sample collected 24 hours after the meeting was weakly positive for the viral RNA (1.12 × 102 PFU m−3). In conclusion, mask use and vaccination are still the main effective methods for preventing the COVID-19 Omicron variant in indoor environments. Unvaccinated children are a significant source of air contamination and risk further transmission of COVID-19.